Application of Differentiated Instruction on Japanese Language Proficiency Test to Build Students’ Awareness of Lifelong Learning - Asmarani, Dhaniar (Universitas Pendidikan Indonesia (Indonesia University of Education), 2021)
Along with the rapid development of technology and the occurrence of education 4.0, lifelong learning ability becomes an important element in 21st century learning. Lifelong learning ability consists of the ability to develop strategies and evaluate one’s own learning, to improve knowledge, skills, and competence, so that continuous and sustainability learning habit can be built. By applying lifelong learning, students can evaluate their own learning, recognize their weaknesses and strengths, so that they can design the right learning model for the development of their knowledge. The ability to do lifelong learning is very important to be mastered by a student, so the teacher should introduce this learning model to student. On the other hand, as teacher we also conduct classroom / group learning that the differences in student’s ability may vary in one class. It needs to be facilitated by designing student personal learning (Differentiated Instruction / DI) to maximize student outcome. This paper discusses how DI strategies that implemented in Japanese Language Proficiency Test: Intermediate Level (Noryoku Shiken III) courses can build student awareness of lifelong learning. The participant of this research is the student from Japanese Language Proficiency Test: Intermediate Level (Noryoku Shiken III) class in Japanese Department, in a private university in Jakarta. The result of this research is after applying DI, a good progress was seen in each student towards the achievement of JLPT N3 grades, and can create independent learning habits, so students can sustain this learning habits even after finishing this subject.